Estimation of evaporative fraction and evapotranspiration from remotely sensed data using a complementary relationship - Venturini, Virginia (2007)
Fil: Venturini, Virginia. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.